PENERAPAN MODEL KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPA - Agusta, Arnemmi (Jurnal Pendidikan Guru, 2018)
This study aims to determine the application of Model Talking Stick Co-operative Model can improve the learning outcomes of science on the material special features of animal class VI SDN 20 Pekanbaru. The subjects of this research are the students of class VI SDN 20 Pekanbaru academic year 2016. The number of research subjects are as many as 35 students. Techniques used to collect data in this study are tests, non-tests (Observation / observation, and documentation). This study was conducted by applying the Talking Stick Type Co-operative Model which has been done for two cycles, it can be concluded that the learning by applying the Talking Stick Type Co-operative Model has a positive impact in improving students learning outcomes in the science lesson on the material of special characteristics of animals with value the average student in Cycle I has achieved 88% good category while in Cycle II increased to 94% with very good category and the average value of teacher teacher Cycle I has reached good category 82% and Cycle II has increased to 91% with very good category. Conclusion that Application of Talking Stick Type Co-operative Model can improve science learning outcomes in material of special characteristic of animal of class VI SDN 20 Pekanbaru.